Riplle Mill Machine Failure Analysis Using the Failure Mode and Effect Analysis (FMEA) Method at PT. Ujong Neubok In - Jayarullah; Rita Hartati (LPPM Politeknik Aceh Selatan, 2023)
Palm oil is a plantation crop of high economic value and is one of the crops producing vegetable oil and various other derivative products. Palm oil processing is one of the factors that determine the business productivity of a palm oil mill. The smoothness of the production process is greatly influenced by the reliability of the machines used. The Ripple Mill machine is a meisn that serves as a seed breaker to separate the shell from the palm kernel. This study aims to identify failures that occur in the Ripple Mill engine. This research uses the Failure Mode and Effect Analysis (FMEA) method, which is to find out and observe whether the failure rate can be analyzed or measured so as to minimize the damage / failure. Based on the results of the study, there are 5 failure risks that occur in the Ripple Mill engine with the component that has the highest value is the V-Belt, which is 294 RPN, while the one with the lowest value is the Ripple Plate Pipe with a Risk Priority Number value of 60 RPN.